(untitled) (Web of Teachers: Inderscience Research, 2025)
Disorders of physical development in children with chronic pathology of the digestive system are one of the pressing and complex problems in the field of Medicine. Chronic digestive disorders disrupt the absorption of nutrients in the child’s body and negatively affect general health. As a result, the child’s physical growth rate slows down, less muscle mass development occurs, weight deficiency and many other negative conditions occur.